Assessing left atrial function in patients with atrial fibrillation and valvular heart disease using cardiovascular magnetic resonance imaging. Issue 5 (15th March 2022) - Hou, Jie; Sun, Yu; Zhang, Libo; Wang, Wei; You, Hongrui; Zhang, Rongrong; Yang, Benqiang; Wang, Huishan
Abstract: Background: Atrial fibrillation (AF) is common arrhythmia in valvular heart disease (VHD) and is associated with adverse outcomes. Hypothesis: To evaluate the left atrial (LA) function in patients with AF‐VHD by cardiovascular magnetic resonance imaging feature tracking (CMR‐FT) using LA strain ( ε s / ε e / ε a ) and their corresponding strain rate (SRs/SRe/SRa). Methods: This was a retrospective cross‐sectional inter‐reader and intra‐reader reproducibility conducted from July 1, 2020, to January 31, 2021. A total of 39 patients with AF‐VHD (rheumatic heart valvular disease [RHVD] [ n  = 22], degenerative heart valvular disease [DHVD] [ n  = 17]) underwent MRI scans performed with drug‐controlled heart rate before correcting the rhythm and valves through maze procedure. Fifteen participants with normal cardiac MRI were included as healthy control. ε s /SRs, ε e /SRe, and ε a /SRa, corresponding to LA reservoir, conduit, and booster‐pump function, were assessed using Feature Tracking software (CVI42 v5.12.1). Results: Compared with healthy controls, LA global strain parameters ( ε s / ε e / ε a /SRs/SRe/SRa) were significantly decreased (all p  < 0.001), while LA size and volume were increased in AF‐VHD group (all p  < 0.001). In the subgroup, RHVD group showed lower LA total ejection fraction (LATEF) and strain data than DHVD group (12.6% ± 3.3% vs. 19.4 ± 8.6, p  = 0.001). Decreased LATEF was significantly related to altered LA strain and strain rate, especially in ε s, ε e, and SRs (Pearson/Spearman r/ρ  = 0.856/0.837/0.562, respectively; all p  < 0.001). Interstudy and intrastudy reproducibility were consistent for LA volumetry and strain parameters (intraclass correlation coefficient: 0.88–0.99). Conclusions: CMR‐FT can be used to assess the LA strain parameters, and identify LA dysfunction and deformation noninvasively, which could be a helpful functional imaging biomarker in the clinical treatment of AF‐VHD.